the SAUDI ARABIA AND QATAR RELATIONS ON CONFLICT IN THE MIDDLE EAST REGION - ryan maulana gibran gibran (Universitas Duta Bangsa Surakarta, 2023)
ABSTRACT; Purpose: In this study, it will be studied how big the influence and role of Saudi Arabia and Qatar in the conflicts that occur in the Middle East region. Methodology/approach: In this study, the author uses the library research method by analyzing some of the data that the author takes from books, journals, and other reliable sources. Results/findings: The results of this study are the discovery of threats to political economy stability and Saudi Arabia's national interest over the alliance made by Qatar with Iran. In the conflict that occurred, Qatar strengthened its country's relations with Iran, especially in the realm of production of natural resources, oil and gas, LNG. The LNG cooperation was so successful that it was considered a threat to the stability of Saudi Arabia's oil trade. Limitations: The limitation in this research is because the research method carried out by the researcher uses the library research method. The author realizes that there are several aspects that the author may not be able to analyze. This happens because of the limitations of the authors in obtaining the data sources needed to analyze the topics in this study, namely the influence and role of Saudi Arabia and Qatar in the conflicts in the Middle East. Contribution: Hopefully, this research will become a reference for knowledge about the role and influence of Saudi Arabia and Qatar in the conflicts that occur in the Middle East region. In addition, the authors hope that this research can be used as a reference material for further research to be able to examine aspects that have not been discussed in this study.